2010
DOI: 10.1093/treephys/tpq044
|View full text |Cite
|
Sign up to set email alerts
|

Drought-induced photosynthetic inhibition and autumn recovery in two Mediterranean oak species (Quercus ilex and Quercus suber)

Abstract: Responses of leaf water relations and photosynthesis to summer drought and autumn rewetting were studied in two evergreen Mediterranean oak species, Quercus ilex spp. rotundifolia and Quercus suber. The predawn leaf water potential (Ψ(lPD)), stomatal conductance (gs) and photosynthetic rate (A) at ambient conditions were measured seasonally over a 3-year period. We also measured the photosynthetic response to light and to intercellular CO₂ (A/PPFD and A/C(i) response curves) under water stress (summer) and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
73
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 51 publications
18
73
0
2
Order By: Relevance
“…Similar with some previous studies (Vaz et al 2010), the soluble sugars increased significantly with drought stress, but the increased starch concentration was different from other studies (Naser et al 2010;Silva et al 2010). Gebauer et al (1998) suggested that strong positive correlations exist between soluble sugar and TP concentrations and between starch and condensed tannins concentrations, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…Similar with some previous studies (Vaz et al 2010), the soluble sugars increased significantly with drought stress, but the increased starch concentration was different from other studies (Naser et al 2010;Silva et al 2010). Gebauer et al (1998) suggested that strong positive correlations exist between soluble sugar and TP concentrations and between starch and condensed tannins concentrations, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…However, lack of transpiration blockage can lead to difficulties under prolonged, severe drought (Aussenac, 1984). In contrast, Quercus rotundifolia develops deep rooting structures to access groundwater reserves and maintain high rates of transpiration in combination with stomatal closure under extreme stress (David et al, 2004;Cubera and Moreno, 2007;Vaz et al, 2010). These different strategies leave Cedrus more vulnerable to extended temperature-driven summer drought and low soil moisture.…”
Section: Impacts Of Long-term and Millennial-scale Summer Temperaturementioning
confidence: 99%
“…Decrease in chlorophyll contents was due to decrease in chlorophyll biosynthesis rather than its degradation (Jain et al, 2013). Vaz et al (2010) showed no difference in Q. suber tree leaves from summer to autumn.…”
Section: Discussionmentioning
confidence: 84%